도로 표면 강우 유출 해석 알고리즘 개발 - 조준범(Jun Beom Jo); 김정수(Jung Soo Kim); 곽창재(Chang Jae Kwak) (Ecology and Resilient Infrastructure, 2021)
In general, stormwater flows to the road surface, especially in urban areas, and it is discharged through the drainage grate inlets on roads. The appropriate evaluation of the road drainage capacity is essential not only in the design of roads and inlets but also in the design of sewer systems. However, the method of road surface flow analysis that reflects the topographical and hydraulic conditions might not be fully developed. Therefore, the enhanced method of road surface flow analysis should be presented by investigating the existing analysis method such as the flow analysis module (uniform; varied) and the flow travel time (critical; fixed). In this study, the algorithm based on varied and uniform flow analysis was developed to analyze the flow pattern of road surface. The numerical analysis applied the uniform and varied flow analysis module and travel time as parameters were conducted to estimate the characteristics of rainfall-runoff in various road conditions using the developed algorithm. The width of the road (two-lane (6 m)) and the slope of the road (longitudinal slope of road 1 - 10%, transverse slope of road 2%, and transverse slope of gutter 2 - 10%) was considered. In addition, the flow of the road surface is collected from the gutter along the road slope and drained through the gutter in the downstream part, and the width of the gutter was selected to be 0.5 m. The simulation results were revealed that the runoff characteristics were affected by the road slope conditions, and it was found that the varied flow analysis module adequately reflected the gutter flow which is changed along the downstream caused by collecting of road surface flow at the gutter. The varied flow analysis module simulated 11.80% longer flow travel time on average (max. 23.66%) and 4.73% larger total road surface discharge on average (max. 9.50%) than the uniform flow analysis module. In order to accurately estimate the amount of runoff from the road, it was appropriate to perform flow analysis by applying the critical duration and the varied flow analysis module. The developed algorithm was expected to be able to be used in the design of road drainage because it was accurately simulated the runoff characteristics on the road surface. 일반적으로 도심지에서의 유출은 도로 노면을 따라 유출되어 빗물받이를 통해 우수관거로 배수된다. 따라서 적절한 도로 배수능력의 평가는 도로와 빗물받이 뿐만 아니라 우수관거의 설계에서도 필수적이다. 하지만 도시 도로부의 지형학적 및 수리학적 조건을 반영한 흐름해석 방안에 대한 명확한 기준이 제시되어 있지 못한 실정이다. 그러므로 기존에 적용되던 흐름해석 모형(등류/ 부등류) 및 도달시간 산정방법 (임계/고정)을 분석하여 최적의 도로의 흐름해석 방안이 제시되어야 한다. 본 연구에서는 도로 표면 흐름해석을 위한 알고리즘을 개발하고 등류와 부등류 흐름해석 모형 및 도달시간 산정방법을 매개변수로 적용한 수치적 분석을 수행하여 다양한 도로조건에서의 강우 유출특성을 모의하였다. 도로조건은 국내의 설계기준을 고려하여 2차선 도로의 폭 (6 m)과 경사 (도로 종경사 1 - 10%, 도로 노면경사 2% 및 측구 횡경사 2 - 10%)가 고려되었다. 또한, 도로 표면의 흐름은 노면경사를 따라 측구에서 차집되어 하류부의 빗물받이를 통해 배수되도록 하였으며, 측구의 폭은 0.5 m로 선정하였다. 모의 결과 도로의 유출특성은 도로 경사 조건에 따라 민감하게 변화하였으며, 부등류 해석모형이 도로의 하류부로 강우가 차집되며 변화하는 측구부에서의 유출특성을 반영하여 등류 흐름해석 모형에 비해 최대 23.66%, 평균 11.80% 긴 도달시간과 최대 9.50%, 평균 4.73% 작은 도로 표면 총 유출량을 나타냈다. 따라서, 우수 유출량을 산정하기 위하여 도달시간을 강우의 지속시간으로 반영하는 임계지속시간을 적용한 부등류 흐름해석을 수행하는 것이 적합하다고 판단되었다. 개발된 알고리즘은 다양한 흐름해석 기법을 통합하여 도로 노면에서의 유출특성을 정밀하게 모의하고 있으므로 도로의 배수 설계에 활용이 가능할 것으로 기대된다.